2022
DOI: 10.1002/smsc.202270012
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin Inhibits SARS‐CoV‐2 by Targeting Its 3C‐Like Protease

Abstract: Oridonin Inhibits SARS‐CoV‐2 Oridonin, a natural product extracted from Rabdosia rubescens , possesses a wide range of pharmacological properties, including anti‐inflammatory, anti‐cancer, anti‐microbial, neuroprotection, immunoregulation, etc. In article number 2100124 , Baisen Zhong, Litao Sun, and co‐workers demonstrate that Oridonin targets the SARS‐CoV‐2 3CL protease by covalently binding to cysteine145 in its active pocket to exert an anti‐SARS‐CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
3
6
0
Order By: Relevance
“…Oridonin has been identified as an inhibitor of M pro with an IC 50 value of 4.67 µM, which confirmed a previous study showing its M pro inhibitory activity (IC 50 2.16 µM [ 32 ]). From the literature, it is known that oridonin covalently modifies M pro by targeting Cys145.…”
Section: Resultssupporting
confidence: 86%
“…Oridonin has been identified as an inhibitor of M pro with an IC 50 value of 4.67 µM, which confirmed a previous study showing its M pro inhibitory activity (IC 50 2.16 µM [ 32 ]). From the literature, it is known that oridonin covalently modifies M pro by targeting Cys145.…”
Section: Resultssupporting
confidence: 86%
“…Oridonin has been identified as an inhibitor of M pro with an IC50 value of 4.67 µM, which confirmed the previous study with its M pro inhibitory activity (IC50 2.16 µM [32]), and we learned from the literature that Oridonin covalently modifies the M pro targeting Cys145. M pro crystal structure in complex with oridonin (PDB ID: 7VIC [32],…”
Section: >10supporting
confidence: 88%
“…Some isatin derivatives exhibited strong inhibition effects against 3CL pro , such as 1-(naphthalen-2-ylmethyl)-2,3-dioxoindoline-5-carboxamide, which was a promising compound for developing broad-spectrum anti-coronavirus agents. 236,237 Zhong et al 238 identified that oridonin displayed effective inhibition of SARS-CoV-2 3CL pro activity and bound to 3CL pro via covalent bonding, while inhibiting SARS-CoV-2 in Vero E6 cells with an IC 50 of 4.95 μM, above indicating that oridonin prevented SARS-CoV-2 replication by inhibiting 3CL pro . 239 Most recently, by pharmacophore-oriented semisynthesis combining the pharmacophore of oridonin and a novel scaffold (maoelactone A), Zhou et al 240 created a series of compounds with anti-SARS-CoV-2 activity, where compound 70 inhibited the replication of SARS-CoV-2-affected Vero E6 cells with low EC 50 values.…”
Section: Othersmentioning
confidence: 99%
“…Some isatin derivatives exhibited strong inhibition effects against 3CL pro , such as 1‐(naphthalen‐2‐ylmethyl)‐2,3‐dioxoindoline‐5‐carboxamide, which was a promising compound for developing broad‐spectrum anti‐coronavirus agents 236,237 . Zhong et al 238 . identified that oridonin displayed effective inhibition of SARS‐CoV‐2 3CL pro activity and bound to 3CL pro via covalent bonding, while inhibiting SARS‐CoV‐2 in Vero E6 cells with an IC 50 of 4.95 μM, above indicating that oridonin prevented SARS‐CoV‐2 replication by inhibiting 3CL pro 239 .…”
Section: Naturally Derived Sars‐cov‐2 3clpro Inhibitorsmentioning
confidence: 99%